2018
DOI: 10.3389/fpsyg.2017.02354
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Lexical Pitch Accent on Infant Word Recognition in Japanese

Abstract: Learners of lexical tone languages (e.g., Mandarin) develop sensitivity to tonal contrasts and recognize pitch-matched, but not pitch-mismatched, familiar words by 11 months. Learners of non-tone languages (e.g., English) also show a tendency to treat pitch patterns as lexically contrastive up to about 18 months. In this study, we examined if this early-developing capacity to lexically encode pitch variations enables infants to acquire a pitch accent system, in which pitch-based lexical contrasts are obscured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Unique insights into how language experience shapes phonological knowledge could be gained from studies of non-native and native tone perception that exploit the diversity of lexical tone systems, and probe how a range of contrast types are perceived in relation to prosodic distinctions at higher tiers of the phonological hierarchy. Most prior studies of lexical tone perception by infants and young children, however, have drawn their target stimuli and native listeners from a small set of Asian languages that have contour tone systems, though there are some exceptions (e.g., Yoruba, an African register tone language: Harrison, 2000; Japanese, an Asian pitch accent language: Nazzi et al, 1998; Sato et al, 2009; Ota et al, 2018). The non-native listeners have often been non-tonal L1 speakers naïve to the target tone language, though in a few studies their L1s have been pitch accent languages (e.g., So and Best, 2010) or other contour tone languages (e.g., So and Best, 2010, 2011, 2014; Reid et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unique insights into how language experience shapes phonological knowledge could be gained from studies of non-native and native tone perception that exploit the diversity of lexical tone systems, and probe how a range of contrast types are perceived in relation to prosodic distinctions at higher tiers of the phonological hierarchy. Most prior studies of lexical tone perception by infants and young children, however, have drawn their target stimuli and native listeners from a small set of Asian languages that have contour tone systems, though there are some exceptions (e.g., Yoruba, an African register tone language: Harrison, 2000; Japanese, an Asian pitch accent language: Nazzi et al, 1998; Sato et al, 2009; Ota et al, 2018). The non-native listeners have often been non-tonal L1 speakers naïve to the target tone language, though in a few studies their L1s have been pitch accent languages (e.g., So and Best, 2010) or other contour tone languages (e.g., So and Best, 2010, 2011, 2014; Reid et al, 2015).…”
mentioning
confidence: 99%
“…Another potential limitation of much prior research with young children is that often only discrimination has been tested (e.g., Harrison, 2000; Mattock and Burnham, 2006; Mattock et al, 2008; Yeung et al, 2013; Liu and Kager, 2014; Hay et al, 2015; Cheng and Lee, 2018). However, more recent studies have extended the investigation to word recognition and learning (Singh and Foong, 2012; Singh et al, 2014; Hay et al, 2015), including a number of papers in this Special Topic volume (e.g., Liu and Kager, 2018; Ota et al, 2018; Burnham et al, 2019; and several other papers discussed below). Other recent advances include studies on the developmental relationship between perception of lexical tones and perception of higher-tier linguistic information such as stress and prosody (Quam and Swingley, 2010; Liu and Kager, 2014; Singh and Chee, 2016; Choi et al, 2017; Ma et al, 2017) and paralinguistic features such as pitch variations that convey emotions (e.g., Kager, 2018).…”
mentioning
confidence: 99%
“…For our adult listeners, a pitch change did not seem to hinder word recognition at all. Previous studies investigating Mandarin toddlers found no naming effects in tonal MP conditions [36,38], whereas recent studies with Japanese toddlers did find a naming effect [5,8], suggesting that pitch changes are more detrimental to word recognition in Mandarin than in Limburgian and Japanese. The low frequency of tonal minimal pairs, plus the great amount of surface variation might mitigate the reliance on pitch when learning novel words in Limburgian and Japanese.…”
Section: Discussionmentioning
confidence: 77%
“…These studies yielded mixed results, possibly due to the use of different procedures and different tone contrasts varying in acoustic salience. There is limited research dedicated to the acquisition of lexical tones in more restricted tone systems like Japanese and Swedish [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation